The Trend of Knowledge in Environmental Management for the Elderly in the Disruptive Era - Wisakha Phoochinda, Wisakha; Paron Vongchan, Paron; มาภักดี, กิติภา (Local Administration Journal, 2021)
The purpose of this study was to analyze courses, curricula, and knowledge in environmental management for the elderly in Thailand and other countries in this disruptive era. The author reviewed related curricula, courses, and knowledge and collected primary data through interviews of relevant agencies, as well as a survey and focus group discussion to examine opinions of the elderly in ten provinces. The results show that the content of these sources currently does not pay much attention to environmental education management as a main subject. As a result, the elderly may not see the importance of the environment as they should. The body of knowledge on environmental management for the elderly in this disruptive era should involve the application of local wisdom in environmental management in the community, the development of knowledge transfer, and collaborative learning and their community across generations. There should be environmental management activities for the elderly and their community to build good relationships and promote a learning atmosphere. The learning style could be online as it is appropriate in this disruptive era.